UNIVERSITY, SOCIETY, PRESS AND POLITICS RELATIONSHIP IN THE STUDENT MOVEMENTS OF THE 40s IN THE UNIVERSITY OF CARTAGENA - Piñeres De La Ossa, Dora (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2012)
Student’s movement, press and politics have shown a constant in Colombia through the university’s history. The access to press began as a privilege used as media of publicity which gave the student´s movement representation and leadership in the fight for its ideals. The movement of the forties at the Universidad de Cartagena is not an exception. It was due to this means of communication that its acknowledgement was given and even if it didn’t permit the academic demands, it was interested in becoming part of the political fight of those times. Left-wingers started to arise in Colombian universities and the conservative opposition became more dominant.